Covid-19: Stock market reaction to government interventions in the UK : Industrial analysis - Uusipere, Aleksi Johannes (My University, 2021)
During the Covid-19 pandemic, governments around the globe have carried out unforeseen actions to stabilize the economy and to prevent the virus from spreading. This thesis aims to examine the short-term impact of these government interventions on different stock market sectors in the UK. In addition, interest lies in whether the stock market reaction is more prevalent in the early stages of the pandemic than in the late stages. An Event study methodology is employed to test the semi-strong form of the Efficient Market Hypothesis, which states that all available information, including historic, is already incorporated in the market prices. The data consists of FTSE All-Share index, and ten industry indices that are selected accordingly to the ICB recommendations. The results show that it is clear that the impact of these discussed government interventions is more prevalent in the early stages of the pandemic than what it is later, to similar announcements. Social distancing intervention announcements have a negative impact on all investigated industries except for Oil & Gas, Health care, Telecommunications and Financials industries. Government economic support packages do not have an immediate impact on the stock market, although significant and positive impact is observed in the post-event period. When the UK stock market is compared to the ACWI All-Country index, the impact of these government announcement is negative and significant for all investigated events. The results indicate that industries that are dependent on real economic activity, react negatively and significantly to government imposed social distancing measures. This negative reaction can be alleviated by government support packages, but the effect is not always present. As the epidemic progresses, the negative impacts of government interventions become less negative while the positive impacts become more positive.

Covid-19 pandemian aikana valtiot ovat määränneet ennennäkemättömän määrän eristämistoimenpiteitä viruksen leviämisen estämiseksi sekä valtiontukia talouselämän tukemiseksi. Tämä tutkimus pyrkii selvittämään, millainen vaikutus näillä vastatoimenpiteillä on Iso-Britannian osakemarkkinoihin ja miten eri sektorit näihin reagoivat. Tämän lisäksi tarkastellaan, onko markkinareaktio erilainen pandemian alkupuolella kuin mitä se on myöhemmin pandemian edetessä. Tässä tutkimuksessa käytetään Event study -metodologiaa ja testataan Tehokkaiden markkinoiden keskivahvoja ehtoja, joiden mukaan kaikki saatavilla oleva informaatio, sekä historiallinen informaatio on jo sisällytettynä markkinahintoihin. Aineisto koostuu FTSE All-share osakeindeksistä sekä sen kymmenestä eri sektori-indeksistä, jotka on valittu ICB-suositusten mukaisesti. Tulokset osoittavat, että pandemian alussa markkinat reagoivat huomattavasti voimakkaammin valtion väliintuloihin kuin myöhemmässä vaiheessa. Viruksen leviämistä hidastavat toimenpiteet, kuten ulkonaliikkumiskiellot, vaikuttavat negatiivisesti kaikkiin toimialoihin, lukuun ottamatta öljyn & kaasun, terveydenhuollon, tietoliikenteen sekä rahoituksen toimialoja. Valtion taloustukiin osakemarkkinat eivät reagoi välittömästi, mutta merkitseviä ja positiivisia epänormaaleja tuottoja havaitaan tapahtuman jälkeisellä tarkkailujaksolla. Vastatoimenpiteiden vaikutus Iso-Britannian osakemarkkinaan suhteessa muun maailman osakemarkkinoihin on merkitsevästi negatiivinen kaikissa tutkituissa tapahtumissa. Tutkimustuloksista voi päätellä, että reaalitaloudesta riippuvaiset toimialat kuten yleishyödykkeet tai kuluttajien palvelut reagoivat voimakkaasti ja negatiivisesti tartuntojen ehkäisyyn määrättyihin toimenpiteisiin. Tätä negatiivista reaktiota voidaan yrittää lievittää valtion taloustukien muodossa. Pandemian edetessä valtion väliintulojen negatiiviset vaikutukset lievenevät ja positiiviset vaikutukset vahvistuvat.
Keywords: COVID-19; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance